Rewiring carbon flow in Synechocystis PCC 6803 for a high rate of CO2-to-ethanol under an atmospheric environment - Gao, E-Bin; Wu, Junhua; Ye, Penglin; Qiu, Haiyan; Chen, Huayou; Fang, Zhen (Frontiers in Microbiology, 2023)
Cyanobacteria are an excellent microbial photosynthetic platform for sustainable carbon dioxide fixation. One bottleneck to limit its application is that natural carbon flow pathway almost transfers CO2 into glycogen/biomass other than designed biofuels such as ethanol. Here, we used engineered Synechocystis sp. PCC 6803 to explore CO2-to-ethanol potential under atmospheric environment. Firstly, we investigated the effects of two heterologous genes (pyruvate decarboxylase and alcohol dehydrogenase) on ethanol biosynthesis and optimized their promoter. Further, the main carbon flow of ethanol pathway was strengthened via blocking glycogen storage and pyruvate-to-phosphoenolpyruvate backflow. To recycle carbon atoms escaped from tricarboxylic acid cycle, malate was artificially guided back into pyruvate, which also created NADPH balance and promoted acetaldehyde converting into ethanol. Impressively, we achieved high-rate ethanol production (248 mg/L/day at early 4 days) via fixing atmospheric CO2. Thus, this study exhibits the proof-of-concept that rewiring carbon flow strategies could provide an efficient cyanobacterial platform for sustainable biofuel production from atmospheric CO2.